Analisis Struktural Naskah Drama Bila “Malam Bertambah Malam” Karya Putu Wijaya - Jelita Maulida Nurhamidah; Rita Rismawati; Adita Widara Putra (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
This study examines the importance of structural analysis in understanding the depth of a literary work, particularly the drama script "Bila Malam Bertambah Malam" by Putu Wijaya. Through a systematic approach, this research identifies and analyzes intrinsic elements such as theme, plot, characters, setting, language style, dialogue, and message in the drama script. The method of structural analysis is employed to comprehend how these elements interact and contribute to the overall meaning of the literary work. The findings of this research reveal the complexity of the messages conveyed by Putu Wijaya, especially concerning social class issues and the conflict between love and traditional norms. The research findings can serve as a useful reference source in Indonesian language learning at the high school level, enriching the understanding of literature, and contributing to the development of Indonesian literary studies. Although structural analysis provides a deep understanding of the literary work, there is still room for further research to comprehend other aspects of the drama script and its implications in the context of literature and literary education.